Diagnostic and predictive value of serum transferrin receptors in non-transfusion-dependent thalassemia: a case–control study - Rania Soliman Hamza; Amina Abdel-Salam; Ahmed Mohamed Moussa; Dalia Mohamed Ahmed Helal (Egyptian Pediatric Association Gazette)
Abstract Background Non-transfusion-dependent thalassemia (NTDT) is a significant global health issue that affects nearly 90 million individuals worldwide. NTDT is a form of chronic anemia that can lead to bone pain, deformities, and hepatosplenomegaly. Soluble transferrin receptor-1 (sTfR) is proposed as a biomarker to assess NTDT severity and predict blood transfusion requirements, yet its diagnostic value remains unclear. This study aimed to evaluate the role of sTfR as a diagnostic and predictive marker for NTDT severity and blood transfusion requirements. This case–control study included 34 NTDT and 33 healthy controls matched for age and sex. Diagnosis was made based on clinical examination, hemoglobin (Hb) electrophoresis, high-performance liquid chromatography (HPLC), and genetic testing. sTfR and serum transferrin were measured; also, sTfR/ferritin ratio was reported. Results NTDT patients showed a significantly higher levels of sTfR (1201.56 ± 892.43 nmol/L) and serum ferritin (171.04 ± 17.92 ng/mL) compared to the healthy control group (p < 0.001). The sTfR/ferritin ratio was significantly lower in NTDT patients (0.26 ± 0.27) compared to the healthy control group (0.46 ± 0.14) (p < 0.001). Additionally, a strong positive correlation was found between sTfR levels and blood transfusion frequency, with a sensitivity and specificity of 100% at a cutoff of ≥ 196.2 nmol/L (AUC = 1.00). Serum ferritin also showed diagnostic value but with lower sensitivity and specificity (62.96% and 57.14%, respectively). Conclusion This study suggests that sTfR may assist in evaluating NTDT severity and transfusion needs, potentially supporting clinical decision-making if validated in future studies.